A Rare Presentation of Retiform Hemangioendothelioma in the External Auditory Canal. (13th July 2014) - Jothi, Ezhil Arasan; Sundaram, Muthuchitra; Namasivayam, Jeyalakshmidevi; Jothi, Mathivanan
Abstract : Retiform hemangioendothelioma is a rare intermediate or borderline neoplasm of the blood vessels that mostly occurs in extremities. Here we report a unique case of retiform hemangioendothelioma presented in the external auditory canal. 58-year-old male patient presented with the complaint of right ear swelling for 4 years. On examination, a spherical swelling in the right ear was found occluding the view of external auditory canal. The tumor was removed surgically. Intraoperatively, the mass was found attached to the outer part of the right external auditory canal near the root of helix. Histopathology of the resected tumor showed typical features of retiform hemangioendothelioma. In addition, immunohistochemical analysis revealed that tumor was positive for endothelial cell marker CD34 and occasionally positive for cell proliferative marker Ki-67.